HUBUNGAN RESPON IMUN HUMORAL DAN DERAJAT TROMBOSITOPENIA PADA KEJADIAN DEMAM BERDARAH DENGUE - Halasan Sitohang, Orion; Darmanta Sembiring, Budi; Marpaung, Alexander (Jurnal Kedokteran Methodist, 2022)
Background : DHF is a rapidly infectious disease, especially in tropical as well as subtropical areas. DHF spreads quickly, because the agent of DHF in the form of dengue virus enters through the human body through the bites of the Aedes aegypti and Aedes albopictu mosquitoes. Reported dengue hemorrhagic fever, the number of reported world cases increased by 2.2 million in 2010 to 3.34 million in 2016. Currently, dengue hemorrhagic fever is still clinical and laboratory criteria in the form of thrombocytopenia of less than 100,000/μl. Examination of hemoglobin, leukocytes, It is necessary to calculate the type of peripheral blood smear and liver enzymes such as SGOT and SGPT in addition to platelets to obtain more information to support the diagnosis of Dengue Hemorrhagic Fever. Dengue Hemorrhagic Fever is established based on serological examinations, one of which is IgM and IgG examinations. The sensitivity and specificity of this examination is quite high in determining the presence of Dengue Hemorrhagic Fever infection. This examination is needed to distinguish fever caused by the dengue virus or fever due to other causes and also to distinguish primary and secondary Dengue Hemorrhagic Fever. Methods: This research is a research with a literature study method or literature review. The literature review is a comprehensive overview of research that has been done on a specific topic from various sources of journals, books, documentation, internet and libraries. Conclusion: Based on several journals that have conducted literature studies of the relationship between the humoral immune response and the degree of thrombocytopenia in dengue hemorrhagic fever, it can be concluded that there is a relationship between the humoral immune response and the degree of thrombocytopenia in the incidence of dengue hemorrhagic fever